2005
DOI: 10.1002/pola.21084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclic methacrylic acid oligomers by atom transfer radical polymerization

Abstract: Poly(methacrylic acid) (PMAA) oligomers were synthesized by combining template polymerization and copper‐mediated atom transfer polymerization with multivinyl monomer of β‐cyclodextrin (CD) having 20.4 methacryloyl groups on both primary and secondary hydroxyl group sides of CD scaffold, with 1,3‐dibromobutane as an initiator. The initiation and propagation sites of polymerized sequence of β‐CD were connected by postpolymerization of polymerized products with CuBr and tris[(2‐dimethylamino)ethyl]amine (Me6TREN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Since the oligomers are formed from a templation of monomeric units around b-cyclodextrin, control of the ring-size is limited. 29,30 The cyclic amphiphilic polymer reported herein represents a new class of amphiphilic polymers in which the amphiphilic arms emanate from a cyclic polymer ''core.'' Owing to the flexibility of the monomer, the conformations of these polymer micelles in solution should be extremely dynamic and dependant on solvent (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since the oligomers are formed from a templation of monomeric units around b-cyclodextrin, control of the ring-size is limited. 29,30 The cyclic amphiphilic polymer reported herein represents a new class of amphiphilic polymers in which the amphiphilic arms emanate from a cyclic polymer ''core.'' Owing to the flexibility of the monomer, the conformations of these polymer micelles in solution should be extremely dynamic and dependant on solvent (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, few MS studies have been reported for PMAA and most of them focused on the analysis of volatile thermal degradation products of the polymer [33,34]. Intact PMAA oligomer ions could be produced by matrix assisted laser desorption/ionization (MALDI) [35][36][37][38]. Although mass averages from these MS data were often biased to low molecular weight and produced with poor signal-to-noise ratios, information regarding absolute masses of each individual macromolecular species was available, allowing monomer and end-group masses to be confirmed.…”
mentioning
confidence: 99%
“…However, there are few examples of the characterization of poly(methacrylic acid) (PMAA) homopolymers by MALDI-TOFMS in the literature. The analytical protocols used in positive ion mode are 2,5-dihydroxybenzoic acid (DHB) matrix in methanol [4] or DHB and sodium trifluoroacetate in acetone [5]. Sinapinic acid in methanol (MeOH) or water (H 2 O) has been used in negative ion mode [6].…”
mentioning
confidence: 99%